Basic density and shrinkage of Scots pine (Pinus sylvestris L.) thinning wood - Stöd, Reeta; Marttila, Juhani; Haapala, Antti; Tomppo, Laura; Verkasalo, Erkki (Springer Nature, 2025)
The basic density and shrinkage properties of Scots pine wood from commercial first and second thinning-stage forests were studied in eastern Finland with a reference from final-felling forests. Linear mixed model analysis was applied, indicating statistically significant differences in basic density between stand types and forest site types, with significant effects of cambial age and height position. Additionally, the 2-level interaction terms between site type, cambial age and height position were significant. In Myrtillus type sites, the basic density was 380 kg/m3 for first-thinning wood, and 407 kg/m3 and 406 kg/m3 for second-thinning and final-felling wood, respectively. Young thinning trees showed, on average, wider growth rings (2.83 mm) compared to mature trees (2.04 mm). Density and latewood proportions increased with tree age, particularly in poor site types, whereas the growth ring width had opposite effects. Significant differences were observed in radial, tangential and volumetric shrinkage across stand types, height positions and radial positions, while the longitudinal shrinkage model indicated statistically significant differences between radial positions only. The radial shrinkage was 4.04% in the first thinnings and 4.44% in the second thinnings, while the tangential shrinkage was 6.98% and 7.16%, respectively. The substantial variation in properties, particularly in the first thinnings, likely reflected the presence of juvenile wood, stem form defects and reaction wood in the harvested material, making it less suitable for mechanical processing. The results confirmed that the properties of second-thinning wood enable its use in applications requiring higher density and allowing reasonable shrinkage.
Keywords: scots pine; wood; basic density